Use of Tregs as a cell‐based therapy via CD39 for benign prostate hyperplasia with inflammation. Issue 9 (19th March 2020) - Jin, Xi; Lin, Tianhai; Yang, Guang; Cai, Huawei; Tang, Bo; Liao, Xinyang; Li, Huifang; Chen, Xiaoting; Gong, Lina; Xu, Hang; Sun, Yi; Tan, Ping; et al.
Abstract: Benign prostatic hyperplasia (BPH) occurs most commonly among older men, often accompanied by chronic tissue inflammation. Although its aetiology remains unclear, autoimmune dysregulation may contribute to BPH. Regulatory T cells (Tregs) prevent autoimmune responses and maintain immune homeostasis. In this study, we aimed to investigate Tregs frequency, phenotype, and function in BPH patients and to evaluate adoptive transfer Tregs for immunotherapy in mice with BPH via CD39. Prostate specimens and peripheral blood from BPH patients were used to investigate Treg subsets, phenotype and Treg‐associated cytokine production. Sorted CD39 +/− Tregs from healthy mice were adoptively transferred into mice before or after testosterone propionate administration. The Tregs percentage in peripheral blood from BPH patients was attenuated, exhibiting low Foxp3 and CD39 expression with low levels of serum IL‐10, IL‐35 and TGF‐β. Immunohistochemistry revealed Foxp3+ cells were significantly diminished in BPH prostate with severe inflammatory. Although the Tregs subset was comprised of more effector/memory Tregs, CD39 was still down‐regulated on effector/memory Tregs in BPH patients. Before or after testosterone propionate administration, no alterations of BPH symptoms were observed due to CD39‐ Tregs in mice, however, CD39 + Tregs existed more potency than Tregs to regulate prostatic hyperplasia and inhibit inflammation by decreasing IL‐1β and PSA secretion, and increasing IL‐10 and TGF‐β secretion. Furthermore, adoptive transfer with functional Tregs not only improved prostate hyperplasia but also regulated muscle cell proliferation in bladder. Adoptive transfer with Tregs may provide a novel method for the prevention and treatment of BPH clinically.